Study on the Influence of Grid Voltage Quality - Guiping Yi; Renjie Hu (Institute of Advanced Engineering and Science, 2014)
Industrial Static Var Generator (SVG) is typically applied at or near the load center to mitigate voltage fluctuation, flicker, phase unbalance, non-sine distortion or other load-related disturbance. Special attention is paid to the influence of grid voltage quality on SVG current, the non-sine distortion and unbalance of grid voltage causes not only the AC current distortion and unbalance but also the DC voltage fluctuation. In order to let the inverter voltage contain the fundamental negative sequence and harmonic component corresponding to the grid voltage, a new dual-loop control scheme is proposed to suppress the influence in this paper. The harmonic and negative sequence voltage decomposition algorithm and DC voltage control are also introduced. All these analyses can guide the practical applications. The simulation results verify the feasibility and effectiveness of the present control strategy and analyses.